A novel approach for determining criteria weights: application in ranking materials for mechanical manufacturing processes - Duc Trung Do; Dung Hoang Tien; Bao Nguyen Chi; Van Duc Duong (Manufacturing Review)
Material selection is a complex challenge within Multi-Criteria Decision-Making (MCDM). This research introduces SIWEC-ROC, a novel two-stage weighting method combining SIWEC and ROC to ensure stable material rankings across various MCDM techniques. The method first employs SIWEC to determine initial criterion weights and ranks, then applies ROC to calculate final weights based on these ranks. Validated across four mechanical engineering cases, including weighting for ranking gear materials, cutting tool materials, automotive protective plate materials, and EDM powders, SIWEC-ROC consistently demonstrated superior ranking stability compared to SIWEC alone. For example, average Spearman coefficients significantly improved: Case 1 showed 0.9563 for both SIWEC and SIWEC-ROC, Case 2 from 0.8368 to 0.9114, Case 3 from 0.8167 to 0.8667, and Case 4 from 0.8869 to 0.9212. The advantages of SIWEC-ROC over SIWEC were even clearer during sensitivity analysis. Using SIWEC-ROC allows engineers to quickly identify optimal materials, saving time, effort, and cost by reducing trial machining and boosting overall efficiency.